2017
DOI: 10.1177/2158244016676294
|View full text |Cite
|
Sign up to set email alerts
|

A SERVQUAL-Based Framework for Assessing Quality of International Branch Campuses in UAE

Abstract: The quality of education provided in management institutions is a matter of debate in every country. With a rapid growth in the economy, the quality of management education provided in the United Arab Emirates (UAE) has also been a topic in the forefront. The burgeoning growth in this sector, with mushrooming "branch campuses" from around the world in the UAE, has led policy makers to reflect on the importance of quality of management education being imparted. The main purpose of this article is to explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 35 publications
4
23
0
3
Order By: Relevance
“…The higher education industry has not been exempted from either high competition and student's demand for excellent service quality [2,3]. Currently students have a wide range of universities services to pick from and better service quality indeed influences a university competitive advantage as well [1,4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher education industry has not been exempted from either high competition and student's demand for excellent service quality [2,3]. Currently students have a wide range of universities services to pick from and better service quality indeed influences a university competitive advantage as well [1,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Service quality is considered an important factor for higher education institutions. However, most of the research studies were focused on the Malaysia [6,7], India [1,8], UAE [5,9] UK, [3,10], and Africa [2,11], and very few studies has been undertaken to measure service quality of universities in Pakistan. Therefore, it is very important for organizations to possess knowledge about the student's' behaviour and satisfaction in order to deliver better service quality to its student's.…”
Section: Introductionmentioning
confidence: 99%
“…These may be applicable to different categories of services (Mauri et al, 2013). Based on the bibliography (Datta & Vardhan, 2017;Đonlagić & Fazlić, 2015;Green, 2014). We have adapted these five dimensions to services offered by a Moroccan engineering school.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a study in the United Arab Emirates (UAE) with 300 students, examined the five dimensions of the SERVQUAL model at seven different campus universities in the UAE (Datta & Vardhan, 2017). The main results revealed that services with higher quality difference fall under assurance.…”
Section: Service Quality In An Engineering Schoolmentioning
confidence: 99%
“…TNHE programs are accredited by the Ministry of Higher Education's Center for Academic Accreditation. Many of the institutions operate in the free zones of the country such as the Dubai International Academic City and the Knowledge Village in Dubai (Datta & Vardhan, 2017).…”
Section: Tnhe In the United Arab Emiratesmentioning
confidence: 99%